Analisis Aspek Pemasaran Dalam Studi Kelayakan Bisnis - Iir Tsamrotur Rofa; Ade Rizki Meilani; Nur Mija an Hasibu; Ahmad Kurnia Nasution; Suhairi Suhairi (VISA: Journal of Vision and Ideas, 2021)
Composing this article plans to decide the possibility of business in business in Indonesia. For this situation the creator utilizes an attainability examination through investigation of market and advertising angles. furthermore the outcomes acquired in the part of appropriate showcasing, specifically with excellent items, great unrefined components at reasonable costs so it will goodly affect business clients, in particular all individuals of the local area can get it. furthermore advancements, as we realize that the limited time job that business clients give is to the point of making customers know what items are being sold. Keywords: Feasibility Study of Business, Market, and Marketing Aspect